Depressive Symptoms in Late Pregnancy Disrupt Attentional Processing of Negative–Positive Emotion: An Eye-Movement Study - Tang, Weina; Bao, Ciqing; Xu, Ling; Zhu, Jie; Feng, Wenqian; Zhang, Wenmiao; Lin, Cong; Chen, Lan; Cheng, Qianqian; Ding, Penghao; Zhou, Meixi; Bao, Ying; et al. (Frontiers in Psychiatry, 2019)
This study investigated biases for negative-positive information in component processes of visual attention (initial shift vs. maintenance of gaze) among women in late pregnancy with or without depressive symptoms. Eye movements were recorded while participants viewed a series of picture pairs depicting negative, positive, and neutral scenes. Initial orienting (latency and percentage of first- fixation) and gaze duration were computed. Compared with neutral pictures, the group with major depressive symptoms (MDS) were less able to sense the positive emotion-related pictures and were over-responsive to negative emotion-related pictures. The group with suspicious depressive symptoms (SDS) had an attention bias toward both positive and negative emotion-related pictures. The group with no depressive symptoms (NDS) had an attention bias toward positive emotion-related pictures and had an initial attention avoidance tendency for negative emotion related pictures. The initial gaze direction bias score for negative emotion-related pictures was positively correlated with the severity of depressive symptoms. Therefore, women with a risk of perinatal depression have a significant bias toward negative stimuli. Hypervigilant emotion processing during pregnancy may increase a woman’s the susceptibility to depression during late pregnancy. Attention away from negative information or attention towards positive information may provide a way of buffering emotional responses.